O gênero crônica: um estudo sob o enforque da teoria da estrutura retórica em interface com a linguistica textual - Emanuel da Silva Fontel (2019)
The Brazilian chronicle took on a particular form with its newspaper debut in the 19th century: it is no longer a historical report, a current format of the chronicle in many other cultures, but rather a genre in the sphere of the debate around political, social, cultural, existential and aesthetic issues, among others, which arise from trivial, everyday experiences. The texts of the Brazilian chronicle usually articulate stylistic aspects of both Literature and Journalism; they are written in everyday language and sometimes reveal the authors disposition to interact directly with the reader; as a rule, they show typological heterogeneity. Although recurrent, these traits do not seem enough to properly characterize the chronicle. The fact that there are innumerable categories of the genre (we could identify approximately thirty of them), based on a great variety of criteria, some of which completely different one from the other, is emblematic of the situation. Therefore, this doctorate dissertation aims at contributing to a more suitable characterization of the Brazilian chronicle. For that, we analyze a corpus of twenty chronicles, focusing on prototypical arrangements of their rhetorical structure as established by Rhetorical Structure Theory RST. These arrangements constitute yet another parameter that can characterize the genre, together with other well established references in the studies of the Brazilian chronicle. The theoretical/ methodological framework is built at the interface of Functionalism and Textual Linguistics. More specifically, from the functionalist point of view of the Rhetorical Structure Theory -RST, we follow the pioneering work of Mann and Thompson (1983, 1988, 2000) and of Matthiessen and Thompson (1988), among others developed thereof, such as the work of Taboada (2006, 2009), Redeker e Gruber (2014), Decat (1993, 2010a, 2010b, 2012, 2015) and Antonio (2003, 2004, 2009). On the other hand, from the point of view of Textual Linguistics, we assume the proposals by Coutinho (2007, 2009) and Coutinho and Miranda (2009) for the notion of genre parameters according to a bakhtinian view of discourse genres, especially as disposed in Bakhtin/Volochínov (2014/1929) and Bakhtin (2011/1979). We also resort to Bronckart (1996, 2007, 2010) for the definition of discursive worlds and of the discourse types that semiotize the texts. Brown and Yule (1983), Jubran et al. (1992) and Jubran (2006) also integrate the theoretical/methodological framework as an RST methodological imperative, which demands segmentation into units of information, in the present study, to determine the discursive topic, or the units among which the rhetorical relations are established. As for the investigation of a chronicles features, we resorted to classic scholars of Brazilian and Portuguese literature, such as Coutinho (1971), Candido, (1992), Arrigucci (1987), and also to others, who have reviewed the theme: Calhoub, Neves and Pereira (2005), Neves (2007), Costa (2014), Reis (2015) and Gabriel Jr. (2015). The hypothesis, which has been confirmed, is that the following rhetorical relations are present in the texts of the Brazilian chronicle: Preparation, Attribution, Background, Evidence and Justification. The results demonstrate that at topic level II, where the individualizing topics are found, there are regular arrangements that function at the generic level, i.e., at the level of the features that create individualization due to the relative stability of the genre. The results reveal a network of rhetorical relations, defined by the establishment of Preparation, Attribution and Background at the beginning; Evidence, Justification, Elaboration, Sequencing, List and Contrast along development; and Assessment, Summary and Justification at the end of the genre. Besides suggesting this compositional format, we defend that this network of rhetorical relations is valid in the sense that it connects with various aspects of the theme and allows language users to realize multiple socio-discursive purposes within the social and ideological spheres where the genre circulates.